Precarious employment at a young age and labor-market marginalization during middle-adulthood: A register-linked cohort study - Thern, Emelie; Matilla-Santander, Nuria; Bodin, Theo; Hemmingsson, Tomas (Scandinavian Journal of Work, Environment & Health, 2023)
' ' OBJECTIVE ': 'The present study aims to investigate the association between exposure to precarious employment three years after graduation and the risk of labor market marginalization (LMM) ten years later. ' ' METHODS ': 'A registered-linked cohort study based on the Swedish Work, Illness, and Labor-market Participation (SWIP) cohort was conducted among all individuals born between 1973 and 1976, who were registered in Sweden the year they turned 27 years old (N=365 702). Information on the exposure of labor market establishment three years after graduating from school and outcome of LMM ten years after graduating was collected from nationwide registers. Relative risk ratios (RRR) with 95% confidence intervals (CI) were obtained by multinominal logistic regression. ' ' RESULTS ': 'After considering important covariates, young adults in precarious employment three years after graduation were at an increased risk of future long-term unemployment (RRR 2.31), later precarious employment (RRR 2.85), and long-term sickness absence/disability pension (RRR 1.43) compared to individuals who had obtained standard employment arrangements within three years of graduating. Young precariously employed men had a slightly strong association compared to females with regards to all outcomes. ' ' CONCLUSION ': 'The result of this study suggests that both young men and women in precarious employment three years after graduation are more likely to have a weaker attachment to the labor force later in life compared to individuals of the same age in standard employment. This is important as the prevalence of precarious employment is increasing globally, and young adults appear to be especially vulnerable.
Keywords: cohort study; disability pension; labor-market marginalization; precarious employment; register data; sick leave; sickness absence; unemployment; young adult; young employee; young worker